Outage performance of UAV-assisted relaying MIMO-NOMA networks with SWIPT in Rician fading channels - Cagiran, Harun; Kucur, Oğuz; Büyükçorak, Saliha (Elsevier Gmbh, 2025)
In this work, we consider unmanned aerial vehicle (UAV)-assisted simultaneous wireless information and power transfer (SWIPT)-based non-orthogonal multiple access (NOMA) system with imperfect successive interference cancellation (ipSIC) over Rician fading channels. The base station (BS) and ground users (GU) have multiple antennas applying maximal ratio transmission and maximal ratio combining diversity techniques, respectively, and communicate via a single-antenna UAV that performs amplify-and-forward relaying and power splitting (PS). Closed-form outage probability expressions are derived and validated through Monte Carlo simulations in a probabilistic path loss model. Additionally, system performance is analyzed asymptotically. Numerical results show that the optimum altitude and horizontal position of the UAV vary by urban density, and the optimum PS ratios are distinct between NOMA users. The optimum altitude fora certain urban density does not change by antenna configurations and ipSIC conditions. Adding antennas to the BS results in more performance gain than increasing antennas on the GUs. When the numbers of antennas on the BS and GUs are equal, the optimal horizontal position of the UAV is quite close to the BS; however, as the number of BS antennas increases, this position shifts closer to the GUs, a notably pronounced shift for the far user.
Keywords: Non-orthogonal multiple access (NOMA); Simultaneous wireless information and power; transfer (SWIPT); Unmanned aerial vehicle (UAV); Multiple-input multiple-output (MIMO); Amplify-and-forward (AF) cooperation